Research progress on the effect of paralysis-relieving exercise on the function of the affected limbs in patients with rheumatoid arthritis (通痹操对类风湿关节炎患者患肢功能影响的研究进展) - ZHAO Jialu (赵佳璐); WANG Chun (王纯); TANG Ling (唐玲); WANG Huaxin (王华新); WANG Jianing (汪嘉宁) (Journal of International Translational Medicine Limited, 2023)
The rheumatoid arthritis can contribute to high rate of teratogenicity and disability, which is an internationally recognized major refractory disease. Starting from the current domestic research status, this paper reviewed the studies on effect of paralysis-relieving exercise on the function of the affected limbs in patients with rheumatoid arthritis from five perspectives including biomechanics, Traditional Chinese Medicine five major organs theory, exercise physiology, rehabilitation medicine and sports medicine, and provided reference for expanding treatment options for rheumatoid arthritis. (类风湿关节炎(RA)致畸和致残率高, 是国际公认的重大难治性疾病。本文从目前国内研究现状出发, 从生物力学、中医五脏角度、运动生理、康复医学和运动医学五个维度总结通痹操对RA患者患肢功能的影响, 旨在为进一步拓展RA治疗方案提供参考。)